(untitled) (Journal of Scientific Research, 2018)
Present study aspires at the design of an immediate release formulation with prospective use of fexofenadine hydrochloride by exploring the effect of sodium starch glycolate as super disintegrant. Fexofenadine hydrochloride immediate release tablets (Formulations F-1, F-2, F-3, F-4 and F-5) using different ratios of sodium starch glycolate as a disintegrant were prepared by direct compression method. Standard physicochemical tests were performed for all the formulations. Dissolution studies of the formulations were done in phosphate buffer, pH 6.8 using USP apparatus II (paddle apparatus) at 50 rpm. Percent release of fexofenadine hydrochloride of formulations F-1, F-2, F-3, F-4 and F-5 were 89.98%, 90.98%, 92.95, 96.92% and 99.85%, respectively after 1 h and the release pattern followed the zero order kinetics. The release rate in the formulation F-5 was higher compared to other formulations and the studied market products. Sodium starch glycolate speed up the release of the drug from the core tablets, and the release of fexofenadine hydrochloride from tablets was directly proportional to the amount of sodium starch glycolate present in the formulations and there by produced immediate action.